2017
DOI: 10.3390/ijms18102080
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Chronic Kidney Disease Associated with High Salt Intake

Abstract: High salt intake has been related to the development to chronic kidney disease (CKD) as well as hypertension. In its early stages, symptoms of CKD are usually not apparent, especially those that are induced in a “silent” manner in normotensive individuals, thereby providing a need for some kind of urinary biomarker to detect injury at an early stage. Because traditional renal biomarkers such as serum creatinine are insensitive, it is difficult to detect kidney injury induced by a high-salt diet, especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…The endocannabinoids that level is enhanced during hypertension [40] through activation of cannabinoid receptor may modulate ROS generation [41] , [42] . However, enhanced ROS generation enhances the inflammatory response and endothelial dysfunction, which can trigger the development of hypertension [3] and lead to kidney metabolic disorders [43] , [44] . The analysis of the functional parameters shown in this and previous study [16] suggests that the chronic administration of URB597, a FAAH inhibitor, in contrast to acute administration, does not prevent hypertension, particularly in rats with spontaneous hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoids that level is enhanced during hypertension [40] through activation of cannabinoid receptor may modulate ROS generation [41] , [42] . However, enhanced ROS generation enhances the inflammatory response and endothelial dysfunction, which can trigger the development of hypertension [3] and lead to kidney metabolic disorders [43] , [44] . The analysis of the functional parameters shown in this and previous study [16] suggests that the chronic administration of URB597, a FAAH inhibitor, in contrast to acute administration, does not prevent hypertension, particularly in rats with spontaneous hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey showed that the overall prevalence of CKD in China was 10.8% (Zhang et al, 2012). Inappropriate lifestyle habits, especially dietary habits such as excessive salt intake, accelerate CKD via blood pressure (BP)dependent and -independent mechanisms (Hosohata, 2017). A number of clinical studies demonstrated that high sodium intake was associated with CKD progression in patients in early stages of CKD (Nerbass et al, 2015;Leonberg-Yoo and Sarnak, 2017;Malta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Generally, salted vegetables are considered detrimental to cardiovascular health because an excessive intake of salt can cause health problems, including hypertension, cardiovascular disease, and others. [13] However, the salted radish also presents a health effect in reducing the blood pressure of rats, which might be because it still contains polyphenols, arginine, -linolenic acid, and other unknown antihypertension substances. [10] Moreover, Lactobacillus fermentum CQPC05 in salted Sichuan pickles can decrease serum TC and TG in high-fat diet-fed mice.…”
Section: Introductionmentioning
confidence: 99%